Avaliação de modelo de misturas aplicado à classificação de impressões digitais segundo a arquitetura pcasys - Atencio, Anibal Cotrina (2010)
Currently, biometric recognition systems have achieved great development and has been used in various fields including trade, finance and security. In the specific case of fingerprint recognition, automatic fingerprint identification systems (AFIS) are able to identify individuals located in large databases, dealing with tens of millions of samples, giving rise to a very high computational cost. Thus, the classification of fingerprints is an important problem to be treated as it reduces the search time by an individual, reducing the search space to a particular subgroup. In this study we assessed if, for the architecture of fingerprint classification known as PCASYS (Pattern-Level Classification Automation System), it is possible to assume that classes can be modeled using Gaussian probability density function and can achieve classification results that can be compared with those obtained with more mature techniques such as those based on neural networks. For this, it is used the Gaussian mixture models (GMM), with supervised and unsupervised approaches in parameter estimation task. It was evaluated the results comparing the rates of misclassification of the proposed technique with the results achieved with other techniques, anyway, we analyzed statistically the estimated parameters of Gaussian mixture models using hypothesis testing and mutual entropy. It was tested using the image bank fingerprints of number 4 of National Institute of Standards and Technology (NIST) considering the 4 class problem and 5 class problem considering the natural distribution and balanced distribution.